Pemberdayaan Masyarakat Berbasis DEI oleh PT Pertamina Patra Niaga Integrated Terminal Semarang - Cantika Caramina Gusma; Heni Indrayani; Luthfi Nurwafi F (Mediakom : Jurnal Ilmu Komunikasi, 2026)
Social inequality in the coastal community of Tanjungmas Village, North Semarang, remains a significant issue encompassing environmental, economic, social, educational, and health aspects, including cases of domestic and gender-based violence. In response to these challenges, corporations are expected to implement social responsibility programs that go beyond financial objectives and address community needs. This study aims to analyze the implementation of a Diversity, Equity, and Inclusion (DEI)-based Community Engagement program at the Integrated Terminal of PT Pertamina Patra Niaga and examine community perceptions of the program. This research employed a qualitative case study approach, using in-depth interviews with community leaders, volunteers, government representatives, and company officers, as well as document analysis. The findings indicate that the Lawang Cemoro program applies DEI principles by involving diverse community groups, particularly vulnerable populations, and improving access to social and economic services. Community Engagement is reflected in three key aspects: content (capacity-building and rights-based training programs), sources (collaboration among community members, local government, and the company), and process (program planning, publication through mass media and social media, implementation of community development programs, suistainability reporting). The program also contributes to the achievement of Sustainable Development Goals. This study highlights the importance of integrating Diversity, Equity, and Inclusion principles into Community Engagement strategies to foster inclusive and sustainable community empowerment.